2018
DOI: 10.29333/ejgm/93470
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between quality of learning experiences and academic burnout among nursing students of Shahid Beheshti University of Medical Sciences in 2015

Abstract: Introduction: While attending in university have pleasant experiences for many students, academic activities will lead to academic burnout for some of them. Obviously, academic burnout will have negative effects on mental, psychological and physical well-being of students. The purpose of this study was to determine the relationship between quality of learning experiences and academic burnout among nursing students of Shahid Beheshti University of Medical Sciences in 2015.Method: This descriptive-correlational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…With the following exceptions, the studies used a version of the Maslach Burnout Inventory to measure burnout: Aghajari et al ( 45 ) used Bersow's Academic Burnout Inventory; Bulfone et al ( 47 ) used the Scale of Work Engagement and Burnout (SWEBO): Chamberlain et al ( 48 ) and Mason and Nel ( 50 ) used a version of PROQOL; Frögéli et al ( 39 ) used the Scale of Work Engagement and Burnout; Kong et al ( 49 ), Wang et al ( 54 ) and Wang et al ( 53 ) used the Academic Burnout Scale; Njim et al ( 51 ) used the Oldenburg Burnout Inventory; and Nurhidayati et al ( 52 ) used the Burnout Questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the following exceptions, the studies used a version of the Maslach Burnout Inventory to measure burnout: Aghajari et al ( 45 ) used Bersow's Academic Burnout Inventory; Bulfone et al ( 47 ) used the Scale of Work Engagement and Burnout (SWEBO): Chamberlain et al ( 48 ) and Mason and Nel ( 50 ) used a version of PROQOL; Frögéli et al ( 39 ) used the Scale of Work Engagement and Burnout; Kong et al ( 49 ), Wang et al ( 54 ) and Wang et al ( 53 ) used the Academic Burnout Scale; Njim et al ( 51 ) used the Oldenburg Burnout Inventory; and Nurhidayati et al ( 52 ) used the Burnout Questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…Aghajari et al ( 45 ), Akansel et al ( 46 ), and Kong et al ( 49 ) all commented that an interest in nursing or the choice of this field of study as first option were significant factors in reducing susceptibility to burnout. In this respect, too, Tomaschewski-Barlem et al ( 29 ) and De Vasconcelos et al ( 31 ) found that burnout was more likely when the student was more inclined to abandon the study course.…”
Section: Resultsmentioning
confidence: 99%
“…Academic success in nursing students is commonly measured as grade point average (GPA) (Wambuguh et al, 2016), as a score obtained on some exams (Wambuguh et al, 2016) or as the completion of the academic programme (Bulfone, De Maria, et al, 2021;Lancia et al, 2018;Wambuguh et al, 2016). Variables affecting academic success in nursing students can be distinguished by sociodemographic such as age, gender, working status and family commitment (Dante et al, 2015); pre-academic, as the grades in secondary school certifications (Dante et al, 2015;Wambuguh et al, 2016); academic, as scores in pre-admission tests, clinical training examination grades (Bulfone, De Maria, et al, 2021); and psychological, such as self-efficacy (Bandura, 1977;Bouih et al, 2021;Bulfone, De Maria, et al, 2021;Schneider & Preckel, 2017) and burnout (Aghajari et al, 2018;Maslach, 1998).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…This is not surprising as nursing students are not entirely engaged to study processes only, but also in learning experiences across different health care settings and patients. The consequences of burnout are not limited to academic achievements, as they may also impact a student's future jobs (Aghajari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, burnout syndrome ( 1 ) and sleep problems ( 2 ) among students have been indicated as a public health concern, due to the repercussions on learning and on the biopsychosocial-spiritual health of these individuals ( 3 ) . Students in the health area and, especially, in Nursing, are very vulnerable due to the characteristics of their training, permeated by conflicts with colleagues and professors, concerns and difficulties in acquiring the necessary knowledge to become good professionals, enter the labor market and provide direct assistance to the patients, who may be in distress ( 4 - 5 ) .…”
Section: Introductionmentioning
confidence: 99%